Wedding Gift Exchange: а comparative Analysis of Gift Exchange in the Context of Kalmyk and Kazakh Culture (Journal of Philosophy Culture and Political Science, 2025)
The article is devoted to the phenomenon of gift exchange as an important social and cultural phenomenon that influences interpersonal and intercultural relations. The author explores the historical aspects of gift exchange, emphasizing its functions in different societies, from strengthening tribal and social ties to the manifestation of respect and solidarity between people. The paper analyzes the types of gifts, their symbolism and meanings, and examines the role of gift exchange in rituals such as weddings. Particular attention is paid to the interaction between the tangible and intangible aspects of gift exchange, as well as to the non-verbal communication that accompanies the gift-giving process. The exchange of gifts in wedding rituals plays a significant role in strengthening social and family ties, as well as in the symbolic confirmation of the intentions of the parties. The article focuses on the study of wedding gift exchange as an important ritual in different cultures, including in the context of Kazakh and Kalmyk traditions.  In Kazakhs and Kalmyks, as well as in many Turkic-language peoples, gift-giving was one of the forms of communication and had one of the important material and symbolic meanings in the establishment and maintenance of social ties. The wedding gift exchange among Kazakhs and Kalmyks is an important part of a traditional wedding, reflecting the respect and mutual obligations between the families of the bride and groom. Attention is paid to the subject of the gift, its symbolism, the process of presenting gifts, the order, and the material value of these things. The wedding gift exchange symbolizes the union of two clans and the unification of their material and spiritual resources. In this paper, the wedding gift exchange in Kazakh culture is compared with that in Kalmyk culture. The study is based on a cultural approach, which allows us to consider the wedding gift exchange as part of a system of symbolic actions that consolidate social ties and cultural values. The main method was literary analysis, aimed at the comprehension of theoretical concepts of gift exchange and the interpretation of ethnographic descriptions.Keywords: wedding ceremony, gift exchange, Kazakh traditional culture, Kalmyk traditional culture, material and symbolic side of a gift, cultural communication, social interaction, everyday culture.